Skin Reactions in Patients With Multiple Sclerosis Receiving Cladribine Treatment. Issue 3 (May 2021) - Rolfes, Leoni; Pfeuffer, Steffen; Hackert, Jana; Pawlitzki, Marc; Ruck, Tobias; Sondermann, Wiebke; Korsen, Melanie; Wiendl, Heinz; Meuth, Sven G.; Kleinschnitz, Christoph; Pul, Refik
Abstract : Objective: To report 77 patients with multiple sclerosis (MS) who developed skin-related adverse events (AEs) following treatment with cladribine. Methods: We evaluated our prospective bicentric cladribine cohort. Cladribine-treated patients with a skin AE were identified. Results: Two hundred thirty-nine cladribine-treated patients with MS were evaluated. Seventy-seven patients (32%) showed at least 1 skin AE at median 1 month after cladribine initiation (range: 1–12). Within first 3 months following last cladribine exposition, hair thinning (n = 28, 12%), skin rash (n = 20; 8%), mucositis (n = 13, 5%), and pruritus (n = 6, 3%) were observed. Furthermore, 35 patients (15%) developed herpes virus infections (time since last cladribine exposition: median 83 [range: 10–305]). In 15 patients, herpes zoster infection was severe (CTCAE grade ≥ 3) and required hospitalization. Delayed skin AEs (≥3 months after a cladribine treatment cycle) involved 1 case of leukocytoclastic vasculitis and 2 cases of alopecia areata. Finally, 2 patients presented with in total 3 isolated precancerous lesions (1 leukoplakia simplex and 2 actinic keratosis) and 1 patient developed a squamous cell carcinoma. Conclusion: Skin AEs are common in patients with MS treated with cladribine. Until risk management plans have been adjusted to include these phenomena, clinicians should perform a thorough clinical follow-up and in suspicious cases seek early interdisciplinary support. In light of the observed delayed skin reactions, we further emphasize the necessity of careful clinical surveillance of cladribine-treated patients for yet undescribed secondary autoimmune events. Classification of Evidence: This study provides Class IV evidence that skin-related AEs are frequent in patients with MS following cladribine in a real-world setting.